THE EFFECT OF INFANT MASSAGE ON NUTRITIONAL STATUS AND INFANT SLEEP QUALITY IN INFANTS AGED 0 – 6 MONTHS IN THE CHILDREN'S CLINIC AT HAJI HOSPITAL, EAST JAVA PROVINCE - Awwalul Wiladatil Qodliyah; Umi Ma’rifah; Herlina; Dewi Rimasari; Arif Wijaya Rusli (Rena Cipta Mandiri, 2025)
This study was motivated by the need for optimal nutrition and the need for good sleep quality in infants to support their growth and development. This study aims to determine the effect of infant massage on nutritional status and sleep quality in infants aged 0-6 months. The research design was a quasi-experimental design with a non-equivalent control group design. The study population was infants aged 0-6 months who had low nutritional status and sleep quality at the Haji Hospital in Surabaya. Based on the table above, it can be interpreted that of the 12 infants who received infant massage in the control group and the experimental group, there was a significant effect with a p-value of 0.004 <α 0.05 on sleep quality. While for the nutritional status of the experimental group, a p-value of 0.003 <α 0.05 was obtained. In this study, it was concluded that there was a significant effect of giving infant massage on the sleep quality of infants aged 0-6 months. The researchers found that the quality of infant sleep had increased, where after the infant massage, the poor quality of infant sleep decreased, from 5 infants (41.7%) to 0 infants (0%). This is also seen in the category of good baby sleep quality, increasing significantly from 2 babies (16.7%) to 12 babies (100%) after baby massage. There is a significant effect of giving baby massage on the nutritional status of babies aged 0–6 months.